Classroom management techniques for teaching English inclusively to adhd and asd primary students in Vietnam - Ha, Vu Hai (H. : ĐHQGHN, 2020)
Recently included in general education as a compulsory subject since Grade 3, English has established itself in Vietnam as a crucial foreign language for the people to communicate effectively in a globalization era. As a result, English language teaching for primary students has drawn increasing attention from various educators and researchers. However, their studies and teaching practices often overlook students with Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder (ADHD and ASD) - two of the most popular mental disorders in children. In this regard, this mixed-method case study explores the challenges facing, and the solutions the teachers of ADHD and ASD students in Vietnam have been actively drawing on to facilitate their classroom management. After conducting survey questionnaires with 109 English language teachers from 20 cities located in the three regions of Vietnam, the study proceeded with a series of interviews with teachers along with in-class observations. The results indicate that despite these prevailing difficulties, teachers were able to formulate teaching techniques to showcase plenty of innovativeness and versatility in terms of classroom management, despite certain occurrences of potential harmful acts due to the lack of special education training. The discussion could carry useful implications for researchers and teachers working with ADHD and ASD students in Vietnam.